TL in K2SO4 crystals with impurity nickel and manganese ions - Kuketayev, T.A.; Baltabekov, A.S.; Murat, Zh.M.; Sultanov, A.A. (Recent Contributions to Physics, 2012)
In work the recombinational luminescence of K2SO4-Mn and K2SO4-Ni crystals is studied. It is established that impurity ions forms the radiation induced centers and influence on distribution lightsum on TL peaks of a matrix. It is communicated with unradiation defects in crystals. On this influence it is established that ions of manganese and nickel replace cations to a crystal lattice of potassium sulfate selectiv.